Modern vision of Roman Jakobson’s classical theory of indexical symbols - A. Voronova (Ибероамериканские тетради)
Despite active implementing of Roman Jakobson’s classical term «indexical symbol» relating to pronouns, the analysis of Charles Pierce’s theory, which is the pillar of Jakobson’s ideas, puts this term in doubt. As Pierce’s works have defined approaches to any language research so far, their study is relevant due to the growing role of communication.The Theoretical Background of this article is Pierce’s theory of signs, the statements of which are conferred with Jakobson’s ideas using analytical-comparative method.The Study Procedure includes exposition and analysis of Jakobson’s theory five statements.The Study Results are the substantiation of their nonderivability from Pierce’s theory considering modern scientific knowledge logic.1,4. Pronouns are linked to the object denoted conventionally and existentially, so they are indexical symbols.The objects of pronouns and nouns (symbols) are different. Unlike a noun a pronoun doesn’t denote a class of things.Index existential relation doesn’t combine with conventional and ontological symbol relations, creating instead of relations between a sign and an object a vector of attention focusing on a real object having concrete coordinates as incentive to revise a symbol ontological aspect.2. «I» means «person uttering «I».It’s true from the viewpoint of the other person denoting an uttering person as «he/she». If we consider «I» to be a symbol, a person denoting himself/herself like «I», opposes to himself/herself himself/herself as a person whom he/she can denote like «he/she», which is logically inacceptable. And the evident «neighborhood» of Index and Symbol and the latent presence of Symbol in the evident Index are impossible in Pierce’s system.3. Any shifter has its own general meaning.According to Pierce, Indexes have a general meaning, but Symbols have a general meaning and a general concept.5. Indexical symbols overlap code and message.In Jakobson’s theory a code is a sign system, so a pronoun can be any sign. Summarizing, by contrast with Jakobson’s theory of «indexical symbol», Pierce’s ideas allow distinguishing symbol and index considering their objects and character of their relation with objects and define peculiarities of symbol and index interaction in language and speech, so they seem promising for studying a sign nature of pronouns.